SOSIALISASI OLAHRAGA CRICKET KEPADA GURU OLAHRAGA SE-KABUPATEN BOGOR - Aldrin Muhammad Putera; Hasan Basri; Dindin Abidin (An-Nizam, 2022)
This paper describes the results of the Community Service Program on the socialization of cricket to sports teachers. The underlying problem is that there are still many sports teachers who do not know about cricket. One area that lacks knowledge about cricket is Bogor Regency. While this cricket sport has a very large opportunity to support one's achievements. Cricket is a team sport that can be played by all ages, both children, teenagers and the general public. This cricket sport is usually competed in regional and national sports events. Currently, the sport of cricket in Indonesia is in the socialization stage so that the development of cricket is important to be promoted and introduced to all circles, especially to sports teachers. Introduction to sports teachers is very important because cricket needs to be instilled in children from an early age. The purpose of this activity is to provide an overview and rules of the game of cricket to sports teachers in order to get an understanding and practice well according to the theory and rules of the game in the game of cricket.